Effects of Multimodal Analgesia on the Success of Mouse Embryo Transfer Surgery - Parker, John M. (American Association for Laboratory Animal Science, 2011)
Multimodal analgesia is promoted as the best practice pain management for invasive animal research procedures. Universal acceptance and incorporation of multimodal analgesia requires assessing potential effects on study outcome. The focus of this study was to assess effects on embryo survival after multimodal analgesia comprising an opioid and nonsteroidal antiinflammatory drug (NSAID) compared with opioid-only analgesia during embryo transfer procedures in transgenic mouse production. Mice were assigned to receive either carprofen (5 mg/kg) with buprenorphine (0.1 mg/kg; CB) or vehicle with buprenorphine (0.1 mg/kg; VB) in a prospective, double-blinded placebo controlled clinical trial. Data were analyzed in surgical sets of 1 to 3 female mice receiving embryos chimeric for a shared targeted embryonic stem-cell clone and host blastocyst cells. A total of 99 surgical sets were analyzed, comprising 199 Crl:CD1 female mice and their 996 offspring. Neither yield (pups weaned per embryo implanted in the surgical set) nor birth rate (average number of pups weaned per dam in the set) differed significantly between the CB and VB conditions. Multimodal opioid–NSAID analgesia appears to have no significant positive or negative effect on the success of producing novel lines of transgenic mice by blastocyst transfer.